If alpha and beta are the zeroes of a polynomial p (x)= 3x^2-5x + 6 find alpha/beta
Answers
Answered by
5
Hey There!!
Here, we are given a quadratic polynomial.
![p(x)=3x^2-5x+6 p(x)=3x^2-5x+6](https://tex.z-dn.net/?f=p%28x%29%3D3x%5E2-5x%2B6)
and
are zeros.
![\text{Sum of zeros } = \alpha+\beta = -\frac{(-5)}{(3)} = \frac{5}{3} \\ \\ \\ \text{Product of zeros } =\alpha \beta = \frac{6}{3} =2 \text{Sum of zeros } = \alpha+\beta = -\frac{(-5)}{(3)} = \frac{5}{3} \\ \\ \\ \text{Product of zeros } =\alpha \beta = \frac{6}{3} =2](https://tex.z-dn.net/?f=%5Ctext%7BSum+of+zeros+%7D+%3D+%5Calpha%2B%5Cbeta+%3D+-%5Cfrac%7B%28-5%29%7D%7B%283%29%7D+%3D+%5Cfrac%7B5%7D%7B3%7D+%5C%5C+%5C%5C+%5C%5C+%5Ctext%7BProduct+of+zeros+%7D+%3D%5Calpha+%5Cbeta+%3D+%5Cfrac%7B6%7D%7B3%7D+%3D2)
Also, letÂ
![\frac{\alpha}{\beta} = t \frac{\alpha}{\beta} = t](https://tex.z-dn.net/?f=%5Cfrac%7B%5Calpha%7D%7B%5Cbeta%7D+%3D+t)
Now, consider:
![\implies \frac{t^2+1}{t} = \frac{\left(\frac{5}{3}\right)^2}{2} -2 \\ \\ \\ \implies \frac{t^2+1}{t} = \frac{25}{18}-2 \\ \\ \\ \implies \frac{t^2+1}{t}=\frac{25-36}{18} \\ \\ \\ \implies \frac{t^2+1}{t} = \frac{\left(\frac{5}{3}\right)^2}{2} -2 \\ \\ \\ \implies \frac{t^2+1}{t} = \frac{25}{18}-2 \\ \\ \\ \implies \frac{t^2+1}{t}=\frac{25-36}{18} \\ \\ \\](https://tex.z-dn.net/?f=+%5Cimplies+%5Cfrac%7Bt%5E2%2B1%7D%7Bt%7D+%3D+%5Cfrac%7B%5Cleft%28%5Cfrac%7B5%7D%7B3%7D%5Cright%29%5E2%7D%7B2%7D+-2+%5C%5C+%5C%5C+%5C%5C+%5Cimplies+%5Cfrac%7Bt%5E2%2B1%7D%7Bt%7D+%3D+%5Cfrac%7B25%7D%7B18%7D-2+%5C%5C+%5C%5C+%5C%5C+%5Cimplies+%5Cfrac%7Bt%5E2%2B1%7D%7Bt%7D%3D%5Cfrac%7B25-36%7D%7B18%7D+%5C%5C+%5C%5C+%5C%5C+)
![\implies \frac{t^2+1}{t} = -\frac{11}{18} \\ \\ \\ \implies 18t^2+11t+1=0 \\ \\ \\ \implies 18t^2+9t+2t+1=0 \\ \\ \\ \implies 9t(2t+1)+1(2t+1)=0 \\ \\ \\ \implies (2t+1)(9t+1)=0 \\ \\ \\ \implies 2t+1=0 \qquad OR \,\,\, 9t+1=0 \implies \frac{t^2+1}{t} = -\frac{11}{18} \\ \\ \\ \implies 18t^2+11t+1=0 \\ \\ \\ \implies 18t^2+9t+2t+1=0 \\ \\ \\ \implies 9t(2t+1)+1(2t+1)=0 \\ \\ \\ \implies (2t+1)(9t+1)=0 \\ \\ \\ \implies 2t+1=0 \qquad OR \,\,\, 9t+1=0](https://tex.z-dn.net/?f=%5Cimplies+%5Cfrac%7Bt%5E2%2B1%7D%7Bt%7D+%3D+-%5Cfrac%7B11%7D%7B18%7D+%5C%5C+%5C%5C+%5C%5C+%5Cimplies+18t%5E2%2B11t%2B1%3D0+%5C%5C+%5C%5C+%5C%5C+%5Cimplies+18t%5E2%2B9t%2B2t%2B1%3D0+%5C%5C+%5C%5C+%5C%5C+%5Cimplies+9t%282t%2B1%29%2B1%282t%2B1%29%3D0+%5C%5C+%5C%5C+%5C%5C+%5Cimplies+%282t%2B1%29%289t%2B1%29%3D0+%5C%5C+%5C%5C+%5C%5C+%5Cimplies+2t%2B1%3D0+%5Cqquad+OR+%5C%2C%5C%2C%5C%2C+9t%2B1%3D0)
![\implies t=-\frac{1}{2} \quad OR t=-\frac{1}{9} \\ \\ \\ \\ \implies \boxed{\frac{\alpha}{\beta}=-\frac{1}{2}} \qquad OR \qquad \boxed{\frac{\alpha}{\beta}=-\frac{1}{9}} \implies t=-\frac{1}{2} \quad OR t=-\frac{1}{9} \\ \\ \\ \\ \implies \boxed{\frac{\alpha}{\beta}=-\frac{1}{2}} \qquad OR \qquad \boxed{\frac{\alpha}{\beta}=-\frac{1}{9}}](https://tex.z-dn.net/?f=%5Cimplies+t%3D-%5Cfrac%7B1%7D%7B2%7D+%5Cquad+OR+t%3D-%5Cfrac%7B1%7D%7B9%7D+%5C%5C+%5C%5C+%5C%5C+%5C%5C+%5Cimplies+%5Cboxed%7B%5Cfrac%7B%5Calpha%7D%7B%5Cbeta%7D%3D-%5Cfrac%7B1%7D%7B2%7D%7D+%5Cqquad+OR+%5Cqquad+%5Cboxed%7B%5Cfrac%7B%5Calpha%7D%7B%5Cbeta%7D%3D-%5Cfrac%7B1%7D%7B9%7D%7D)
Hope it helps
Purva
Brainly Community
Here, we are given a quadratic polynomial.
Also, letÂ
Now, consider:
Hope it helps
Purva
Brainly Community
Answered by
3
Hope it helps.............
Attachments:
![](https://hi-static.z-dn.net/files/dfd/a48fb6010ba73d8553460edbb983c296.jpg)
AaanyaKandwal:
thnx
Similar questions
Psychology,
8 months ago
Computer Science,
8 months ago
Math,
1 year ago
English,
1 year ago
English,
1 year ago